Perbaikan Manajemen Sistem Gudang di PT. Dewata Cipta Semesta - Enrico Tjahjono; Felecia Felecia (Jurnal Titra, 2015)
PT. Dewata Cipta Semesta is a company which focused in sawmills, wood products produced in the form of cut (sawn timber) for building’s materials or furniture’s raw materials. The Warehouse system at the company is still very simple and has many weakness that cause some problems in the company such as the difference between the stock and the physical stock in the warehouse as well as the lenght of the process of unloading. Based on observations and data analysis on company, there are some problems that result in differences in stock and phusical as well as the duration of the process of unloading are: the arrangement of goods in the warehouse are not grouped in detail, two warehouses head leads, and grading process is carried out when loading. Warehouse management system improvement is done to minimize the difference between the stock and the physical stock in the warehouse as well as accelerate the process of unloading the goods. Warehouse management system improvements made are arrange of the raw material warehouse are grouped by type and diameter of the timber , the warehouse material classified by type , grade and size of the timber , making the Standard Operating Procedure for the warehouse staff. For make the system running properly also proposed to appoint only one head of the warehouse so that there is clarity on the duties and responsibilities of the warehouse.